VLSI physical design automation : theory and practice - Sait, Sadiq M., 1957- (McGraw-Hill ; IEEE Press [distributor], 1995)
VLSI is an important area of electronic and computer engineering: however, there are few textbooks available for undergraduate education in VLSI design automation and chip layout.